A mariner transposon vector adapted for mutagenesis in oral streptococci - Nilsson, Martin (2014)
This article describes the construction and characterization of a mariner-based transposon vector designed for use in oral streptococci, but with a potential use in other Gram-positive bacteria. The new transposon vector, termed pMN100, contains the temperature-sensitive origin of replication repATs-pWV01, a selectable kanamycin resistance gene, a Himar1 transposase gene regulated by a xylose-inducible promoter, and an erythromycin resistance gene flanked by himar inverted repeats. The pMN100 plasmid was transformed into Streptococcus mutans UA159 and transposon mutagenesis was performed via a protocol established to perform high numbers of separate transpositions despite a low frequency of transposition. The distribution of transposon inserts in 30 randomly picked mutants suggested that mariner transposon mutagenesis is unbiased in S. mutans. A generated transposon mutant library containing 5000 mutants was used in a screen to identify genes involved in the production of sucrose-dependent extracellular matrix components. Mutants with transposon inserts in genes encoding glycosyltransferases and the competence-related secretory locus were predominantly found in this screen.